Web-Based of The Regency Apparatus Work Unit Application at the Communications, Informatics, and Encryption Service of Bireuen Regency in Aceh Province - Rara Audia Utami; Rahma Fitria; Rini Meiyanti; Muhammad Ikhwani; Zalfie Ardian (International Journal of Engineering, Science and Information Technology, 2022)
The Regency Apparatus Work Unit (SKPK) is an apparatus of the Regional Government (Provincial and Regency/City) in Indonesia. SKPK is the executor of executive functions that need to be coordinated for the success of government administration. The legal basis for the formation of the SKPK is in article 120 of Law No. 32 of 2004 concerning Regional Government. The Department of Communication,  Informatics, and Encryption Service (Diskominfosa) is an agency that is fully responsible for processing information within the Government in Indonesia. The purpose of this application is to collect the data in various offices in Bireuen Regency and store it in the database. The system is web-based that uses the PHP framework Codeigniter 3 and also using the Bootstrap framework. Initially, this study applied field research using the interview as the primary data and the Reports of the Evaluation on Accountability Performance at The Regency Apparatus Work Unit of Bireuen District as the secondary data. In developing the application, the waterfall is applied as a software model used. As the result, the application shifted the manual data processing into the system such as filtering the report based on a daily, monthly, and even yearly basis. In addition, they can check the status of their application data by entering the SKPK code that has been made. This SKPK application data collection information system was created with the aim of making data management orderly and checking the status of the Regency Apparatus Work Unit (SKPK) application easier and more precise.